Implementasi Pembelajaran Artificial Intelligence Bagi Siswa Sekolah Dasar di Kota Batu, Malang, Jawa Timur - Lienggar Rahadiantino (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
In today's learning, the development of artificial intelligence designs is a necessity to support the education system. The involvement of artificial intelligence will help students more easily understand lessons in class and facilitate interaction between students and teachers. Through the development of design concepts and learning training, it is expected to be able to encourage the participation of students and teachers to be able to support the learning system in order to obtain better educational outputs through the use of appropriate technology. There are three learning platforms that are used as learning media, including Duolingo, Khan Academy, and Kejarcita. During the implementation of the activity, it was found that students tend to learn faster and enjoy exploring new things. It is hoped that the artificial intelligence learning design through these three applications can help the learning process during the Covid-19 pandemic which requires school from home to continue and run smoothly.